IMPLEMENTASI LESSON STUDY SEBAGAI UPAYA MENINGKATKAN PARTISIPASI AKTIF SISWA DALAM PEMBELAJARAN VIRTUAL - Nova Susanti; Rika Rahmadani Putri (Universitas Jember, 2021)
The outbreak of Covid-19 has resulted in learning activities to be carried out virtually. Based on the experience of implementing virtual learning, students do not participate actively in the learning process. Low student participation in education can be seen from the lack of student responses in answering teacher questions in virtual learning. Based on this problem, the authors researched by implementing lesson study as an effort to increase students' active participation in virtual learning. This study aims to increase students' active involvement in virtual education through the implementation of lesson study. This study's subjects were 32 students of Al Falah Islamic Junior High School class VIII.5 semester 2020/2021 academic year with 13 male students and 19 female students. Implementation of lesson study starts on August 18 to September 1, 2020. This type of research is descriptive quantitative research. Data collection was carried out through student active participation observation sheets. Based on the research results in cycle 1, student participation data obtained an average value of 56.28%. While in cycle 2, the student participation data received an average value of 59.56%.